Graham Patch Versus Modified Graham Patch in the Management of Perforated Duodenal Ulcer - Kidwai, Roman; Ansari, Meraj Alam (Journal of Nepalgunj Medical College, 2017)
Introduction: Peptic ulcer perforation is a serious complication which affects 2-10% of peptic ulcer patients. It presents with an overall mortality of 10% although various authors had reported incidence between 1.3% and 20%. Being a life threatening complication of peptic ulcer disease, it needs special attention with prompt resuscitation and appropriate surgical management if morbidity and mortality are to be contained. Aims and objectives: To compare outcome and complications in Graham patch and Modified Graham patch repair in perforated duodenal ulcer. Material and Methods: A prospective randomized controlled trial was conducted to compare the outcome and complication viz. leakage, obstruction after Graham's patch repair and modified Graham's patch repair undergoing duodenal ulcer perforation in various surgical units of Nepalgunj Medical College Teaching Hospital. Out of these 60 patients; one group (30 cases) underwent Graham's patch repair and another group (30 cases) underwent modified Graham's patch repair. The outcome of procedure was measured in terms of complication like leakage, obstruction and mortality. Results: Duodenal ulcer perforation in group A was more common in male; 58(96.66%) patients were male 2 (3.33%) were female (M:F=29:1). The mean age was 46.80(SD 13.9) years. In Group B it was more common in male; 58(96.66%) patients were male 2(3.33%) were female (M:F=29:1). The mean age was 48.60(SD 14.04) years. Incidence of complication was more common in Group B, no statistically significant difference was found between two groups. The incidence of post operative leakage was 1(3.33%) and in Group B were 2(6.70%). The chi square test was used to compute the p value using SPSS 19. The chi square p value was calculated as 0.554. Hence there was no significant difference between the Group A and Group B. The incidence of burst abdomen was same 2(6.70%) in both the groups. Conclusion: The analysis of results of present study consisting of altogether 60 patients undergoing duodenal ulcer perforation repair showed that Graham's patch repair is as effective as modified Graham's patch repair in terms of morbidity and mortality. Hence there is no statistically significant difference in undergoing either procedure of repair. It is concluded that either procedure can be undertaken depending upon surgeon preference. Journal of Nepalgunj Medical College Vol.13(1) 2015: 28-31